2019
DOI: 10.1007/s00198-019-05215-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of trabecular bone score and prevalent vertebral fractures in women with fragility fractures: a cross-sectional sub-study of NoFRACT

Abstract: Determinants of trabecular bone score (TBS) and vertebral fractures assessed semiquantitatively (SQ1-SQ3) were studied in 496 women with fragility fractures. TBS was associated with age, parental hip fracture, alcohol intake and BMD, not SQ1-SQ3 fractures. SQ1-SQ3 fractures were associated with age, prior fractures, and lumbar spine BMD, but not TBS. Introduction Trabecular bone score (TBS) and vertebral fractures assessed by semiquantitative method (SQ1-SQ3) seem to reflect different aspects of bone strength.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The present study showed that in the studied group, 16 (10.7%) patients had vertebral fractures. This is in agreement with what was previously reported in the study [26], which showed that 33.3% of patients had associated vertebral fracture with the hip fracture while being presenting to emergency services. The presence of a vertebral fracture is a risk factor for subsequent fracture at any given BMD.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that in the studied group, 16 (10.7%) patients had vertebral fractures. This is in agreement with what was previously reported in the study [26], which showed that 33.3% of patients had associated vertebral fracture with the hip fracture while being presenting to emergency services. The presence of a vertebral fracture is a risk factor for subsequent fracture at any given BMD.…”
Section: Discussionsupporting
confidence: 93%
“…Recent work did not find relation between TBS and a vertebral fracture severity index based on VFA; the authors suggested the use of both indices to characterize bone strength [42]. A similar result was found when comparing TBS to quantitative ultrasound (QUS), suggesting that both techniques assess different characteristics of bones [43].…”
Section: Trabecular Bone Scorementioning
confidence: 83%
“… 30 , 31 , 32 , 33 However, there is still a shortage of suitable methods for the focal osteoporosis structural integrity quantification in clinical CT scans. 34 Unlike variogram analysis, such as the Trabecular Bone Score (TBS), which is widely applied in DXA devices for structural integrity evaluation, 35 , 36 , 37 , 38 CT‐based quantification studies drew more attention on apparent microarchitecture estimation. To date, several groups attempted to measure the microarchitecture in multi‐detector CT scanners and revealed its association with osteoporosis status.…”
Section: Discussionmentioning
confidence: 99%